Dry Eye Epidemiology in Patients before Cataract Surgery - S. N. Sakhnov; S. V. Yanchenko; A. V. Malyshev; V. V. Dashina; A. R. Ceeva; L. M. Petrosyan (Oftalʹmologiâ)
Purpose. To evaluate the prevalence, clinical and pathogenetic variants and statistically significant risk factors of dry eye (DE) in patients before cataract surgery. Patients and Methods. 600 age-related and complicated cataract patients (70.6 ± 7.8 years old; 269 men, 331 women) were examined. Visometry and biomicroscopy with photographic recording of the lens state and assessment of its opacities according to the LOCS III classification were used to cataract revealing. OSDI testing, lipid interferential test, TBUT, Shirmer-1, -2 tests, visual and OCT meniscometry, evaluation of epitheliopaty and microerosion (with vital staining), compression Norn test in Korb modification, visual and OCT LIPCOF assessment, lid viper epitheliopathy evaluation, anterior segment of the eye photoregistration with computer morphometry were performed to assess the ocular surface condition. The structure of the DE risk factors, was studied both in DE patients and non-DE subjects with calculation of the Pearson xi-square test. To estimate the strength of the connection between the etiological condition and the DE, the normalized value of the Pearson coefficient (C´) was used. Results. The dry eye prevalence was 53.2 % (of them, 25.5 % was mild, 27.7 % — moderate, by Brzhesky). Subclinical DE prevalence was 27 %. Clinical and pathogenetic variants of mild DE included: isolated lipid deficiency (71.9 %), lipid-mucin deficiency (28.1 %). In patients with moderate DE were identified: aqueous-lipid-mucin deficiency (54.8 %), aqueous-lipid deficiency (37.95 %), isolated aqueous deficiency (7.2 %). The most significant systemic-organ DE risk factors were: diabetes mellitus (C´ = 0.302; in 18.8 % DE patients), female sex (C´ = 0.240; in 62.1 % de patients), allergy (С´ = 0.233; in 23.2 % DE patients). Local risk factors most significantly associated with DE were: meibomian glands dysfunction (С´ = 0.58; in 77.7 % DE patients), chronic blepharitis (С´ = 0.233; in 23.2 % DE patients), pterygium (С´ = 0.276; in 13.2 % DE patients), allergic conjunctivitis (С´ = 0.21; in 21.3 % DE patients). Among the exogenous risk factors, the most significant were: the use of medication affecting tear production or tear film stability (С´ = 0.485; in 89.03 % DE patients), preservative eye drops instillation (С´ = 0.2975; in 56.1 % DE patients). Conclusion. In our opinion, data on the high DE prevalence in cataract patients (53.2 %) should be taken into account when planning cataract surgery, since perioperative correction of the ocular surface condition can increase the surgical treatment efficiency, predictability and safety. The data on the structure of significant risk factors and clinical and pathogenetic DE variants in cataract patients can be the basis for the development of measures to ensure timely DE detection and implementation of reasonable therapy. The risk factor most significantly associated with DE in cataract patients was the meibomian gland dysfunction (MGD) (Pearson xi-square test = 88.542, p < 0.001, С´ = 0.58; “relatively strong” strength). Considering the modifiability of this risk factor (MGD), as well as its high prevalence (77.7 %), it can be considered that eye lids hygiene may be a reasonable therapy in most DE and cataract patients before phacoemulsification.